Group influence on attitudes towards polio vaccination in Pakistan: Role of group identification and perceived group support for polio vaccines - Warda Saleh; Humaira Jami (Journal of the Pakistan Medical Association, 2022)
Objective: To study the moderating role of perceived group normative support on the effect of group identification on scepticism and advocacy domains of attitude towards polio vaccination. Method: The cross-sectional analytical study was conducted at the National Institute of Psychology, Quaid-i-Azam University, Islamabad, Pakistan, in June 2020, and comprised adult residents of Pakistan who were approached through online platform Psytoolkit. Data was collected by means of Attitude towards Polio Vaccination Scale, Group Identification Scale, and a measure of Perceived Group Normative Support for Polio Vaccination. Data was analysed using SPSS 21. Results: Of the 310 participants, 69(22.3%) were men and 240(77.4%) were women. The overall mean age was 25.62+/-8.47 years (range: 18-72 years). Further, 242(78.1%) participants were single and 62 (19.7%) were married, 166(53.45%) were from Punjab, 80(25.8%) from the federally-administered tribal areas, 26(8.3%) from Khyber Pakhtunkhwa, 7(2.2%) from Sindh and 7(1.93%) from Balochistan. Group identification significantly increased advocacy (p<0.001). Perceived group normative support for polio vaccination also increased advocacy (p < 0.01) and was associated with a decrease in scepticism (p< 0.001). Group identification interacted with perceived group normative support for polio vaccination to increase advocacy of polio vaccination (p<0.05). Conclusion: Group identity was found to influence attitudes towards polio vaccination in Pakistan by increasing the persuasive impact of perceived group normative support for polio vaccination. Key Words: Polio vaccines, Attitude towards vaccination, Group identification, Group norms.